ARTIFICIAL INTELLIGENCE IN THE SECURITY STRATEGIES OF THE USA AND CHINA AT THE BEGINNING OF THE 21ST CENTURY – THE STRUGGLE FOR GLOBAL DOMINANCE - Glišin, Vanja (Serbian political thought, 2025)
The development of artificial intelligence (AI) and its increasing application across various sectors of the state and society necessitates monitoring, studying, and actively adopting knowledge and conclusions on the subject across all scientific fields. In recent decades, we’ve observed a comprehensive use of AI in the security strategies of major powers like the United States and China, resulting in a sort of race in developing new technologies and their application. The first part of the paper defines AI, outlines various classifications, and focuses on its use in the security sector. We then analyze the security strategies of the USA and China to identify the role of AI and plans for its development in the global power struggle. Based on this, in the last part of the paper, we present the personalities and differences between the security strategies of the US and China.
Keywords: artificial intelligence; USA; China; security; strategy; Security Strategy